A Rare Case of Primary Vulval Amelanotic Melanoma Involving the Urethra - Montatore, Manuela; Eusebi, Laura; Masino, Federica; Costa, Alessia Mariagrazia; Giannubilo, Willy; Elena, Ferioli; Diamanti, Lucilla; Guglielmi, Giuseppe (Prague medical report, 2024)
A 60-year-old woman came to the Emergency Department complaining of a vaginal formation. The urologist suspected a urethral caruncle: the patient was discharged with vaginal oestrogen cream to relieve symptoms and a follow-up was suggested. After two months the patient returned to the Emergency Department since the mass was increasing in volume and complaining of dysuria and haematuria. Ultrasound, contrast-enhanced computed tomography, and contrast-enhanced magnetic resonance revealed a mass arising from the mucosa and involving the vulva and the urethra, suspicious of malignancy. We present a challenging diagnosis of an infiltrative and rapidly progressive primary vulval amelanotic melanoma with a complete imaging evaluation and a confirmed histological diagnosis.
Keywords: amelanotický melanom; MRI; Melanoma, Amelanotic; CT; lidé; Middle Aged; Amelanotic melanoma vulva; Urethral Neoplasms; Gynecologic tumor; ženské pohlaví; Humans; PVAM; Vulval melanoma; lidé středního věku; nádory močové trubice; Diagnostic procedure; Amelanotic melanoma; Female; Vulvar cancer; Vulvar Neoplasms; AM; nádory vulvy